Understanding the response of the shoulder complex to the demands of repetitive work - McDonald, Alison (My University, 2017)
Repetitive work is common in the workplace and can lead to the development of muscle fatigue. The purpose of this thesis was to improve our understanding of muscular and kinematic adaptation strategies of the shoulder complex throughout the process of fatigue and recovery. To achieve this I completed 6 studies, three studies investigating various aspects of repetitive work and fatigue and three methodological studies that were needed to interpret results. The muscular and kinematic effects of repetitive work were first investigated by incorporating a fatigue protocol between pre- and post-fatigue, simulated, repetitive work (Chapter 2). Fatigue is a complex process and how fatigue develops has been shown to influence its effects. To address this, Chapter 6 and 7 respectively, investigated the response to dynamic and static, fatiguing, repetitive work performed until participants reached termination criteria. Electromyography (EMG) was used throughout this thesis to assess muscle activity, which presented challenges because of its time consuming MVE protocols, the effects of myoelectric fatigue on its interpretation and between participants, fatigue developed in different muscles and at different rates, making comparisons between individuals challenging. For more efficient data collection, a method was developed to reduce the number of maximum voluntary exertions (MVE) required to elicit repeatable, maximum shoulder muscle activity, without eliciting muscle fatigue (Chapter 3). Methods were developed (Chapters 4 and 5) to mitigate the effects of myoelectric fatigue on EMG data and to calculate a multi-muscle fatigue score. This improved interpretation of how prolonged repetitive work impacted load sharing in the shoulder muscles and allowed the calculation of a multi-muscle fatigue score. Overall, this thesis found that the response to repetitive work is complex, multi-faceted and varies between individuals. Repetitive work impacts kinematics, muscle activity, muscle fatigue, strength, affective valence and perceived mental and physical fatigue in both static and dynamic work tasks (Chapters 2, 6, 7). Participants utilized the degrees of freedom in the shoulder complex and use coordinated compensation strategies to maintain their task performance, both following muscle fatigue (Chapter 2) and while developing muscle fatigue (Chapter 6, 7). These responses changed over time, as different muscles fatigued and recovered and were variable between individuals (Chapters 2, 6, 7). Removing fatigue artifacts from the EMG showed that muscle activity changes observed are due to load sharing between the musculature of the shoulder complex (Chapter 6, 7). Participants can adapt to the challenge of fatiguing, repetitive work and individuals will use different, coordinated strategies to maintain task performance.
Keywords: Shoulder, Fatigue, Electromyography, Repetitive Work